Price theory - Ryan, William James Louden; Pearce, David W. (London : Macmillan, 1977)
The revised edition provide undergraduates with a comprehensive introduction to standard price theory. The new chapters on welfare economics and recent developments in microeconomic theory and the expansion of chapters dealing with consumer theory enhances its usefulness in comparison with other textbooks.
Includes bibliographical references and index.
osa 18/01/2019
Loans
Keywords: Microeconomics